Tramando pequenos fios de um longo tecido: as costureiras de Divinópolis - Barreto, Joanice Maria (2010)
The central research question is related to the activities of the seamstresses, sewing women in Divinópolis, MG, whose work is considered a domestic order, a natural aptitude and subject to lower wages. However, by sewing, women ensure the maintenance of home and family, break down stigma in relation to paid work and their role in society. One of the main objectives would be to show that sewing women who are in clothing industries or subcontracting for sewing services, play an important role in the process of economic development of the town, one of the poles of clothing production in the country. To write this dissertation were analyzed published reports in newspapers from the town and nearby region. Apart from written sources, there were made twelve interviews with a group of seamstresses who work in the clothing industry and others who worked in their homes, the professionals who work with subcontracting for sewing services. The collapse of the steel industry in the town and region in 1960 was one of the factors that contributed to women taking over leadership of the economy, trying to reverse the disastrous situation. Considering the situation of many unemployed men, women become visible in the job market through the sewing know-how that was successfully passed from generation to generation. The conquest of women barely changes its position inside and outside their homes. Besides there is a sexual division of labor unfairly and unequally, which still claims that women are responsible for almost all tasks and household chores